Anthropometric and Physiological Characteristics of Elite Male Rugby Athletes. Issue 6 (June 2020) - Brazier, Jon; Antrobus, Mark; Stebbings, Georgina K.; Day, Stephen H.; Callus, Peter; Erskine, Robert M.; Bennett, Mark A.; Kilduff, Liam P.; Williams, Alun G.
Abstract : Abstract: Brazier, J, Antrobus, M, Stebbings, GK, Day, SH, Callus, P, Erskine, RM, Bennett, MA, Kilduff, LP, and Williams, AG. Anthropometric and physiological characteristics of elite male rugby athletes. J Strength Cond Res 34(6): 1790–1801, 2020—This is the first article to review the anthropometric and physiological characteristics required for elite rugby performance within both rugby union (RU) and rugby league (RL). Anthropometric characteristics such as height and body mass, and physiological characteristics such as speed and muscular strength, have previously been advocated as key discriminators of playing level within rugby. This review aimed to identify the key anthropometric and physiological properties required for elite performance in rugby, distinguishing between RU and RL, forwards and backs and competitive levels. There are differences between competitive standards such that, at the elite level, athletes are heaviest (RU forwards ∼111 kg, backs ∼93 kg; RL forwards ∼103 kg, backs ∼90 kg) with lowest % body fat (RU forwards ∼15%, backs ∼12%; RL forwards ∼14%, backs ∼11%), they have most fat-free mass and are strongest (back squat: RU forwards ∼176 kg, backs ∼157 kg; RL forwards ∼188 kg, backs ∼168 kg; bench press: RU forwards ∼131 kg, backs ∼118 kg; RL forwards ∼122 kg, backs ∼113 kg) and fastest (10 m: RU forwards ∼1.87 seconds, backs ∼1.77 seconds; 10 m: RL forwards ∼1.9 seconds, backs ∼1.83 seconds). We also have unpublished data that indicate contemporary RU athletes have less body fat and are stronger and faster than the published data suggest. Regardless, well-developed speed, agility, lower-body power, and strength characteristics are vital for elite performance, probably reflect both environmental (training, diet, etc.) and genetic factors, distinguish between competitive levels, and are therefore important determinants of elite status in rugby.